Genetic diversity in castor (Ricinus communis L.) pistillate lines using EST-SSR markers: GENETIC DIVERSITY IN CASTOR PISTILLATE LINES USING EST-SSR MARKERS - B USHA KIRAN; C LAVANYA (Journal of Oilseeds Research, 2016)
Genetic diversity is essential for crop genetic improvement. Genetic diversity among breeding lines helps breeders in selecting parents for hybrid production with maximumheterosis and combining useful genes in a genetic background. However, heterosis levels in castor hybrids are not up to the desired extent due to narrow range of diversity between male and female lines and development of parents from few common sources. The objective of the study was to assess the diversity and genetic relationship of castor pistillate lines using EST-SSR markers. Sixty percent of the SSR used were polymorphic and 59 alleles were observed with an average of 2.4 alleles per locus. Dice similarity coefficient of UPGMA cluster analysis was used to construct dendrogramand observed five clusters. The Dice coefficient ranged from 0.48 to 0.84. Low level of genetic variation was observed in castor at DNA level with SSR markers.